Using Response Times to Measure Strategic Complexity and the Value of Thinking in Games - David Gill; Victoria L. Prowse (Institute of Labor Economics (IZA), 2017)
Response times are a simple low-cost indicator of the process of reasoning in strategic games (Rubinstein, 2007; Rubinstein, 2016). We leverage the dynamic nature of response-time data from repeated strategic interactions to measure the strategic complexity of a situation by how long people think on average when they face that situation (where we define situations according to the characteristics of play in the previous round). We find that strategic complexity varies significantly across situations, and we find considerable heterogeneity in how responsive subjects' thinking times are to complexity. We also study how variation in response times at the individual level across rounds affects strategic behavior and success. We find that 'overthinking' is detrimental to performance: when a subject thinks for longer than she would normally do in a particular situation, she wins less frequently and earns less. The behavioral mechanism that drives the reduction in performance is a tendency to move away from Nash equilibrium behavior.
Keywords: C72; C91; 330; response time; decision time; thinking time; strategic complexity; game theory; strategic games; repeated games; beauty contest; cognitive ability; personality